Context-Aware Adaptation of Mobile Multimedia Presentations - Weiss, Diana; Helas, Stefan; Martens, Johannes (Electronic Communications of the EASST, 2008)
With increasing capabilities of mobile devices, the number of mobile multimedia services grows steadily. Usage of multimedia services and especially the presentation of multimedia content is more challenging in a mobile environment than on stationary devices due to the diversity of mobile devices and their parameters, the sparse resources of the air interface or the changing context. This position paper introduces an approach for context-aware adaptation of mobile multimedia presentations. For this, a middleware architecture is proposed that performs an automatic and distributed adaptation process: while the server provides a pre-processing of the content, the client completes the overall adaptation. To support this task, the Adaptation Rule Language (ARL) was developed which is introduced in this paper as well.